Teori Servqual dan Customer Satisfaction: Studi Kepuasan Pengguna Layanan Wifi.id Corner - Hermizahadiwidastra, Hermizahadiwidastra; Syamsuar, Dedy (JUSIFO : Jurnal Sistem Informasi, 2022)
For a company, it is important to know the satisfaction of the users of the services that have been provided. The wifi.id corner service has many users, so it is important to know the satisfaction of users of this service because it is one of the parameters for the success of a public service. In this study, the servqual model consisting of 5 dimensions is used, namely tangibles, reliability, responsiveness, assurance, and empathy. Meanwhile, for customer satisfaction in this study, it refers to product quality, service quality, emotional factors, price, cost, and convenience. The purpose of this research is to determine the experience of wifi.id corner users by testing it using the servqual theory, and to know the expectations of users regarding their perception of wifi.id corner. The results of this study indicate that the gap analysis conducted shows that wifi.id corner available in Jambi City does not meet the expectations and standards set in the servqual theory. Therefore, overall, users consider that the wifi.id corner service has not been able to provide satisfaction to customers. In addition, positive value is given by service users towards the respondents' expectations for wifi.id corner service. This indicates that the five dimensions of service quality are considered important by service users.